HISTORY OF THE ACTIVITIES OF THE INTERNAL AFFAIRS BODIES OF MIRISHKOR DISTRICT - Tojiyev Bahodir Movlon oglu (The Conference Hub, 2025)
This scientific article systematically analyzes the formation, historical development stages and modern activities of the internal affairs bodies of Mirishkor district. The work covers the gradual improvement of law enforcement structures in Mirishkor district, which was formed on the basis of the former Usmon Yusupov and Bahoristan districts, the selfless work of leaders and employees, as well as the role of the department's activities in maintaining regional security and public order, based on archival documents and modern sources. The article analyzes the complexity of service conditions, the courage of internal affairs officers, their practical experience in combating crime and preventing offenses. Special attention is paid to the achievements achieved as a result of the reforms implemented during the years of independence, the provision of modern equipment and infrastructure, neighborhood cooperation and preventive work.
Keywords: Mirishkor district, internal affairs bodies, law enforcement, public safety, history, reforms, selfless service, fight against crime, leaders, service conditions, prevention, neighborhood cooperation, modern infrastructure.